#### Answer

See the explanation below.

#### Work Step by Step

Standard equation for ellipse for horizontal major axis is:$\dfrac{(x-h)^2}{a^2}+\dfrac{(y-k)^2}{b^2}=1$
Standard equation for ellipse for vertical major axis is:$\dfrac{(x-h)^2}{b^2}+\dfrac{(y-k)^2}{a^2}=1$
Here, $(h,k)$ represents center with foci $c$ and $c^2=a^2-b^2$
Since, we have $4x^2-9y^2=36$
On dividing both sides by $36$, we get
$\dfrac{x^2}{9}-\dfrac{y^2}{4}=1$
Thus, we can see that the above equation does not match (or, different) with the standard form of an ellipse.